2018
DOI: 10.1038/s41366-018-0175-1
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the complexity of glycaemic health: systematic bio-psychosocial modelling of fasting glucose in middle-age adults; a DynaHEALTH study

Abstract: Background The prevention of the risk of type 2 diabetes (T2D) is complicated by multidimensional interplays between biological and psychosocial factors acting at the individual level. To address the challenge we took a systematic approach, to explore the bio-psychosocial predictors of blood glucose in mid-age. Methods Based on the 31-year and 46-year follow-ups (5,078 participants, 43% male) of Northern Finland Birth Cohort 1966, we used a systematic strategy to select bio-psychosocial variables at 31 years t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…In order to create a composite measure of social disadvantage during early life and adulthood, we used a systematic approach for variable selection as described previously in [19]. Following an inventory of available variables in each dataset, we selected all those, which were an indicator of social disadvantage (a lack of social and economic resources) based on previous literature and a priori knowledge.…”
Section: Social Disadvantage Measures Used In Factor Scoresmentioning
confidence: 99%
“…In order to create a composite measure of social disadvantage during early life and adulthood, we used a systematic approach for variable selection as described previously in [19]. Following an inventory of available variables in each dataset, we selected all those, which were an indicator of social disadvantage (a lack of social and economic resources) based on previous literature and a priori knowledge.…”
Section: Social Disadvantage Measures Used In Factor Scoresmentioning
confidence: 99%
“…Essentially, we must operate data to move beyond association studies and explore how the psychosocial factors, usually classified as confounders in medicine (Figure 2), can be analysed to help their operationalization and integration into healthcare programmes. Despite no apparent consensus in the literature on a single definition of psychosocial health, DynaHEALTH is referring to the following WHO definition 3 as a guiding principle: ‘a state of wellbeing in which every individual realises their own potential, can cope with the normal stresses of everyday life, can work productively and fruitfully, and is able to make a contribution to their community’ 4 , 5 …”
Section: Why Was the Collaboration Set Up?mentioning
confidence: 99%
“…As a result of the use of thiazolidinediones, the risk of bone fractures in postmenopausal women increases [ 15 ]. Finally, recent studies have observed a marked influence of socioeconomic and psychosocial aspects on glycemic health control and a significant association between sociodemographic profile and absolute control of T1DM risk factors [ 59 , 60 ]. Furthermore, T2DM women and men with lower income and education level show poor food choice revealing higher carbohydrate and lower fat intake.…”
Section: Sex Hormones In Endocrine Gender-related Differencesmentioning
confidence: 99%